World outlook origins of the national policy of bolsheviks - Shimov, Vsevolod V. (Journal of the Belarusian State University. Sociology, 2019)
The ideological and historical background of the bolsheviks national policy is considered. It turns out that nationalism and communism correlate as two types of liberation movements at the beginning of the 21st century. The conclusion is made about the internal inconsistency of the Soviet national policy, due to both the contradictions of the worldview of the bolsheviks and the current political situation. The findings can be used in the study of the processes of national construction in the post-Soviet space, as well as in teaching the disciplines of the socio-humanitarian block (political science, history of the Belarusian statehood).
Keywords: nationalism; communism; bolshevism; internationalism